On the development of a deployable cold plasma endoscope - Winter, Jörn; Nishime, Thalita M.C. [UNESP]; Glitsch, Sven; Lühder, Heike; Weltmann, Klaus-Dieter (Wiley, 2018)
A novel non-thermal atmospheric-pressure plasma jet source for endoscopic application is presented. Specific challenges in the endoscopic plasma source development, such as small dimensions, flexibility, operation in half-closed cavities, and the avoidance of in-tube plasma, are addressed. Besides plasma characterization of the jet freely operating in ambient air, special focus is laid on the investigation of in-cavity operation. In order to avoid saturation of the cavity atmosphere with the feed gas and at the same time allow a distinct jet formation, a second gas with electronegative properties is introduced as shielding gas. Depending on the flow rate ratios between feed gas and the shielding gas, arcing and jet-to-glow transition can be suppressed.
Keywords: atmospheric-pressure plasma jet; cavity; endoscope; in-body operation